Evaluation of Efficacy of Budesonide in Prevention of Cardiovascular Risks in Chronic Obstructive Pulmonary Disease Patients (Medical Forum Monthly, 2024)
Background: Cardiovascular disease is a major cause of mortality and morbidity in COPD patients. Systemic inflammation plays a major role in the pathogenesis of cardiovascular disease in COPD. It has, therefore, been suggested that anti-inflammatory agents may prevent cardiovascular disease. it would be plausible that inhaled steroids, such as Budesonide, reduce the local inflammation and subsequent cardiovascular morbidity, thus a local effect on the lung resulting in diminished spill-over of inflammation systemically to the cardiovascular system is an attractive hypothesis.Objective: To assess the impact of Budesonide in reducing the cardiovascular risk in COPD patients.Study Design: Experimental Randomized Study.Place and Duration of Study: This study was conducted in the Department of Pharmacology and Therapeutic, Basic Medical Sciences Institute, JPMC Karachi in collaboration with Department of chest medicine, JPMC, Karachi from Dec. 2010 to March, 2011.Materials and Methods: Thirty five patients with moderate stable COPD, with hsCRP level >3mg/lit, were evaluated in an open label, intention to treat clinical trial. The patients were assigned to give Budesonide (Pulmicort) inhaler 200mcg BD for 12 consecutive weeks. The primary study outcome was to evaluate the reduction in cardiovascular risk by evaluating the improvement in FEV1 and reduction in hsCRP levels, was evaluated at day 30, 60 and day 90.Results: Thirty four (96%) patients were completed the study. At baseline hsCRP levels was 6.68±0.26 which decrease to 5.82±0.20 (P<0.010) at day 90. FEV1(L) at baseline was 2.12±0.05 and at day 90 FEV1 increased upto 2.40±0.04 (P<0.001). This shows that, the Budesonide can statistically significant decrease the hsCRP levels and increase the FEV1.Conclusion: In conclusion, Budesonide effectively decrease the cardiovascular risk by decreasing the systemic inflammation which were indicated by decreasing the hsCRP levels and also improve pulmonary functional capacity in COPD patients.